SULTAN ADAM LAW IN THE PROGRESSIVE LAW PERSPECTIVE IN BANJAR COMMUNITIES IN THE 18TH CENTURY AD - Muhammad Fahmi Al Amruzi; Masyitah Umar; Anwar Hafidzi (Fakultas Syariah UINFAS Bengkulu, 2020)
The Sultan Adam Law provides an important and interesting role in the development of the historyof law in the Banjar land. This happened during the reign of Sultan Adam Al-Watsiq Billah from 1825 to 1857AD. This Law contains matters of religion and worship, issues of Governance Law, Marriage Law, JudicialProcedures, Land Law, and Transitional Regulations. This article discusses the role of the Sultan Adam Lawin the resolution of religious problems in the Banjar community in South Kalimantan and in Progressive law.The findings of this study are that the Law of Sultan Adam became the guide of the judges in deciding cases,becoming a unifying instrument of the kingdom, and an antidote to deviant sect that developed in the 18thcentury AD The Sultan Adam Law also exists as a progressive law, because as a a legal instrument, this lawcan come out of existing traditions and be able to respond to problems that occur in society and always try toconstantly find new meanings and not be bound by absolute meanings. This Law is also able to act as a law thatlives in the midst of society and to meet their needs.